Effectiveness of Integrated Psychological Counseling With Couple Therapy Approach on Quality of Life of Infertile Women - Tayebeh Mokhtari Sorkhani; Atefeh Ahmadi; Moghaddameh Mirzaee; Victoria Habibzadeh; Katayoun Alidousti Shahraki (Guilan University of Medical Sciences, 2022)
Abstract Introduction: Infertility has biological and psychological effects on various aspects of the infertile couple's life. Objective: This study aimed to investigate the effectiveness of integrated psychological counseling with a couple therapy approach on the quality of life of infertile women. Materials and Methods: This clinical trial was conducted on 60 couples (30 couples in the intervention and 30 in the control group) referred to Infertility Center in Kerman City, Iran, from October to December 2018. They were assigned to intervention and control groups with available sampling and block allocation method. The intervention group received six group counseling sessions. The subjects completed the FertiQoL questionnaire before and after the intervention. It has 24 items specific to infertility that cover four subscales of the QoL )emotional, mind-body, relational, and social(. Data analysis was conducted by paired t test, Chi-square test, and Mann-Whitney test. P values less than 0.05 were considered significant. Results: The mean ± SD ages of the participants were 33.25 ± 5.89 and 33.53 ± 5.46 in the intervention and control groups, respectively. Results showed significant differences between the mean ± SD of the mind-body subscale of the intervention group (88.5 ± 6.39) and that of the control group (69 ±12.24), between the social subscale of the intervention group (78± 6.34) compared to that of the control group (60.5 ± 12.27), and between emotional subscale of the intervention group (73.75 ±6.71) compared to that of the control group (54.5 ± 12.29) at the post-test (P =0.001). However, no significant change was seen in the relational subscale of intervention (52.25 ± 6.25) compared to the control group (57.25 ± 12.25) (P= 0.060). Results showed a significantly higher FertiQoL total score for the intervention group (70.56±6.49) compared to the control group (57.76±12.26) at the post-test (P=0.001).  Conclusion: The results indicated that integrated psychological counseling could improve the quality of life among infertile women. Therefore, it can lead to more satisfaction and cooperation in infertility treatment.